2019
DOI: 10.5507/bp.2018.048
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-peptide level correlates with the course of muscle tissue healing in the rabbit model of critical limb ischemia

Abstract: Based on our results, we believe that treatment with ASC-CM has the potential to accelerate the healing process in ischemic tissues in the rabbit model of CLI. The whole healing process was accompanied by miR-126 tissue expression. C-peptide could be used to monitor the course of the tissue healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, the administration of mesenchymal cells that express miR-126 significantly reduces the expression of glucose-induced HMGB1 and the activity of the NLRP3 inflammasome in Primary Renal Mixed Epithelial Cells; 88 as long as it lies upon a critical limb ischemia (CLI) model, treatment with adipose tissue-derived stem cell conditioned medium expressing miR-126 reduces the areas of damage. 89 These facts encourage the assumption that the health status of the diabetic patient is related to the presence of miR-126; therefore, the absence of this miR in serum or plasma could be used as a biomarker of risk linked to hyperinsulinemia in diabetic patients.…”
Section: The Most Frequent Micrornas Reported In People With T2d and Prediabetesmentioning
confidence: 97%
“…Thus, the administration of mesenchymal cells that express miR-126 significantly reduces the expression of glucose-induced HMGB1 and the activity of the NLRP3 inflammasome in Primary Renal Mixed Epithelial Cells; 88 as long as it lies upon a critical limb ischemia (CLI) model, treatment with adipose tissue-derived stem cell conditioned medium expressing miR-126 reduces the areas of damage. 89 These facts encourage the assumption that the health status of the diabetic patient is related to the presence of miR-126; therefore, the absence of this miR in serum or plasma could be used as a biomarker of risk linked to hyperinsulinemia in diabetic patients.…”
Section: The Most Frequent Micrornas Reported In People With T2d and Prediabetesmentioning
confidence: 97%
“…A study of T1DM mice showed that when simvastatin induces skeletal muscle apoptosis, C-peptide can effectively inhibit apoptosis [36]. Tauber et al study has shown that angiogenesis and granulation tissue formation in the early healing stage of non-diabeticrabbit skeletal muscle tissue samples are positively correlated with the level of C-peptide in peripheral blood [37], so it is believed that C-peptide can also be used to monitor the healing process of tissues without diabetes. The mechanism of C-peptide to promote tissue healing is as follows: a) C-peptide inhibits apoptosis through pertussis toxin sensitive pathway [36].…”
Section: Effect Of C-peptide On Tissue Repairmentioning
confidence: 99%